Ways to Enhance Lymphocyte Trafficking into Tumors and Fitness of Tumor Infiltrating Lymphocytes - Bellone, Matteo; Calcinotto, Arianna (Frontiers in Oncology, 2013)
The tumor is a hostile microenvironment for T lymphocytes. Indeed, irregular blood flow, and endothelial cell (EC) anergy that characterize most solid tumors hamper leukocyte adhesion, extravasation, and infiltration. In addition, hypoxia and reprograming of energy metabolism within cancer cells transform the tumor mass in a harsh environment that limits survival and effector functions of T cells, regardless of being induced in vivo by vaccination or adoptively transferred. In this review, we will summarize on recent advances in our understanding of the characteristics of tumor-associated neo-angiogenic vessels as well as of the tumor metabolism that may impact on T cell trafficking and fitness of tumor infiltrating lymphocytes. In particular, we will focus on how advances in knowledge of the characteristics of tumor ECs have enabled identifying strategies to normalize the tumor-vasculature and/or overcome EC anergy, thus increasing leukocyte-vessel wall interactions and lymphocyte infiltration in tumors. We will also focus on drugs acting on cells and their released molecules to transiently render the tumor microenvironment more suitable for tumor infiltrating T lymphocytes, thus increasing the therapeutic effectiveness of both active and adoptive immunotherapies.